2014
DOI: 10.5901/mjss.2014.v5n27p62
|View full text |Cite
|
Sign up to set email alerts
|

Poverty Alleviation in the Northeast Nigeria Mediation of Performance and Moderating Effect of Microfinance Training: A Proposed Framework

Abstract: Poverty is a deficiency in political, social and economic resources. This is caused by lack of employment, capital to establish businesses to earn income, cultural factor, tradition and religion. Women are supposed to be players in assisting their households and in economic growth and development of any nation. Unfortunately, they are prevented as a result of poverty. Microfinance institutions were established for the past decades to help women in fulfilling their dreams of getting out of poverty. These progra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…It is found from related literature that microfinance positively impacts poverty alleviation and is an effective tool for poverty reduction in many countries, including India, Nigeria, Ghana, South Asia, Latin America, the Caribbean, Uganda, Ethiopia, and Tanzania. When implemented and managed carefully, and when services are designed to meet the needs of business actors, microfinance has a positive impact not only on business actors but also on families and the wider community (Belwal et al, 2012;Beisland & Mersland, 2012;Cristabell & Vimal Raj, 2012;Kato & Kratzer, 2013;Kaka & Abidin, 2015;Obadeyi, 2015;Awawory & Marr, 2016;Akingunola, et al, 2018;Fiala, 2018;Khan et al ., 2022;Amanor et al, 2023;Bansah & Adjei, 2023).…”
Section: Literature Review Microfinance Practices Versus Sustainable ...mentioning
confidence: 99%
See 2 more Smart Citations
“…It is found from related literature that microfinance positively impacts poverty alleviation and is an effective tool for poverty reduction in many countries, including India, Nigeria, Ghana, South Asia, Latin America, the Caribbean, Uganda, Ethiopia, and Tanzania. When implemented and managed carefully, and when services are designed to meet the needs of business actors, microfinance has a positive impact not only on business actors but also on families and the wider community (Belwal et al, 2012;Beisland & Mersland, 2012;Cristabell & Vimal Raj, 2012;Kato & Kratzer, 2013;Kaka & Abidin, 2015;Obadeyi, 2015;Awawory & Marr, 2016;Akingunola, et al, 2018;Fiala, 2018;Khan et al ., 2022;Amanor et al, 2023;Bansah & Adjei, 2023).…”
Section: Literature Review Microfinance Practices Versus Sustainable ...mentioning
confidence: 99%
“…Poverty has become a big challenge for nations worldwide, especially for developing countries (Addae-Korankye, 2012; Kaka & Abidin, 2015;Miled & Rejeb, 2018;Mushtaq & Bruneau, 2019). There is a famous global criticism from Mahatma Gandhi: "Poverty is the worst form of violence," which is a creative new approach as an attempt to bargain for the fundamental problems of developing countries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microfinance institutions (MFIs) have the potential to reduce poverty and improve the lives of poor people through microcredit (Thu and Duong, 2018). But the studies show that its impact on livelihood and income of micro-entrepreneur is not significant (Kaka, 2017) and in some cases it becomes even negative despite being a powerful financial tool (Crépon et al, 2015). It shows that for the growth of micro-entrepreneurs only credit is not enough, although it is a critical factor (Mwakalikamo, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Only when those products are used effectively in economic activities can the income level of beneficiaries increase. Several studies have shown the impact of using Islamic microfinance on poverty alleviation, especially the augmentation of income (Farooqi, Qamar, & Chachi, 2017;Kaka et al, 2013;Tafese, 2014;Toindepi, 2016).…”
Section: Previous Studiesmentioning
confidence: 99%